2018
DOI: 10.1007/978-3-319-99978-4_20
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Hand Sign Recognition: Identify Unusuality Through Latent Cognizance

Abstract: Sign language is a main communication channel among hearing disability community. Automatic sign language transcription could facilitate better communication and understanding between hearing disability community and hearing majority. As a recent work in automatic sign language transcription has discussed, effectively handling or identifying a non-sign posture is one of the key issues. A non-sign posture is a posture unintended for sign reading and does not belong to any valid sign. A non-sign posture may aris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…A subsequent study [10] employing a Yolo-based Darknet-19 [11] to simultaneously locate a hand and read a sign has reported mAP 82.06 % also on a single-image setting, but with a complex background. Another study [8] has addressed FSR on a plain background using VGG-16 [12] and reported mAP 97.59 % on a single-image setting, as well as discovered Latent Cognizance-an innovative mechanism to allow an out-of-context awareness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…A subsequent study [10] employing a Yolo-based Darknet-19 [11] to simultaneously locate a hand and read a sign has reported mAP 82.06 % also on a single-image setting, but with a complex background. Another study [8] has addressed FSR on a plain background using VGG-16 [12] and reported mAP 97.59 % on a single-image setting, as well as discovered Latent Cognizance-an innovative mechanism to allow an out-of-context awareness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, we may refer that TFS has 27 multi-posture signings later on). The fact that TFS strongly relies on a multi-posture scheme makes a transcription task ambiguous, e.g., a sequence of TFS signs: 4, 7, 8, and 14 can be transcribed as [4,7,8,14], which all are treated as single postures, resulting "ตหวน" in Thai script, or transcribed as [4,7,8,14], whose first two signs are treated as a multi-posture signing, resulting "ทวน" in Thai script. Our work proposes to address this through a sequence model.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations